Cross-cutting influence of mining commodities on the peruvian economy under a global approach - Gomero Gonzales, Nicko Alberto (2021)
Objective: To analyze how mining activity has transversal impacts on the economy, including financial impacts. Method: Descriptive, correlational-causal, using historical information collected from official sources such as Central Reserve Bank of Peru (CRBP), Chilean Copper Commission (CHICOCO), Lima Stock Exchange (LSE). Results: The study shows that mining has an influence on economic growth (GDP), on tax strength, specifically through the income tax paid by mining companies, and that it stimulates and deepens the capital market through the trading of shares and the prices of these financial assets in the stock market, whose volatility depends on the behavior of the price of mining commodities. Conclusion: Mining, in spite of its environmental liabilities, has direct and transversal effects on the economy, contributing to the process of sustained growth. A result that will translate into the strengthening of globalized markets.